Use of Shells Waste Filler in Pavement Layer Using Lapen (Macadam Penetration Layer) - Kholidia Ayunaning; Avisha Gita P; Kristin Juliati (Procedia of Engineering and Life Science, 2022)
Damage to asphalt construction has made several attempts to increase the strength of asphalt construction, one of which is by utilizing shell waste as an asphalt mixture (filler) which is expected to increase the strength and durability of the pavement. The addition of filler shell waste with varying levels of 0%, 5%, 10%, 15%, 20%, and 25% is taken from the percentage of fine aggregate. Based on the results of the research conducted, the results of the Marshall Test for asphalt mixtures with the best variations of shell waste filler material and meeting the requirements of the General Specifications of Highways were found at a filler content of 0% with an immersion time of 30 minutes, with a VMA (Void in Mineral Aggregate) value. ) 66.07%, VFA (Void Filled with Aggregate) value 66.35%, VIM (Void in Mix) value 21.49%, stability value 1097.15 kg, Flow value 3.04 mm and MQ (Marshall Quotient) value 360.62 kg/mm.